Effect of alcoholic extract of Adhatoda vasica leaves on some biological performance of Ceratitis capitata larvae - Baghdad Science Journal (مجلة بغداد للعلوم)
Many biological tests were done to study the effect of the crude alcoholic leaves extracts on the biological characteristics at the larvae fruit fly Ceratitis capitata with different concentrations of the extracts exposed 1,2,3,5 and 7.5 % at constant laboratory conditions includes the temperature and the relative humidity (27±2C0&70±5 % respectively). The results of the experiments showed that the alcoholic extracts of the plant effected the growth and the development of the larvae and pupae according to the concentrations . The alcoholic extracts proved to have the highest mortality tend to 66.76 % in larva treated with alcoholic at concentration 7.5 % the result also showed that, there was no signifecant differences on the perid of larva pupation that treated with the different concentration.